What Controls the Magnitude and the Shape of Landslide Dam-Breaching Flood Hydrograph? Case Studies of Emergent Forecasts for Outburst Floods of Jiala and Baige Barrier Lakes - Song, Yuntian; Fu, Xudong; Lin, Yongpeng; An, Chenge; Ma, Hongbo (Frontiers in Water, 2022)
Outburst floods released by failing barrier dams are likely to be catastrophic, posing high risk to downstream areas. However, emergent forecasting of the breaching process is still challenging due to the complex mechanisms as well as the lack of adequate data. During October and November 2018, four tremendous barrier lakes formed and breached on the Jinsha River and the Yarlung Zangbo River, China. In this paper, we present numerical simulations for three of these events (October 17 and October 29 at Jiala Village, Yarlung Zangbo; November 3 at Baige Village, Jinsha River), and investigate what factors control the magnitude and shape of the hydrograph of the outburst flood. A physically-based dam-breach model was established for the prediction. We first specified the model parameters based on the aerial images, DEM data and hydrological measurements during the emergency treatment. With these parameters, the model can successfully predict the breaching process of the two barrier dams in the Yarlung Zangpo, but underpredict the peak discharge of the outburst flood in the Jinsha River. The outburst flood in the Jinsha River, however, can be well-reproduced with refined information on dam height and grain size distribution. Moreover, both field data and our numerical simulation showed that the magnitude and shape of the outburst flood hydrograph can be affected by the dam morphology and the composition of dam material. Two patterns of outburst flood hydrographs with different symmetry characteristics were identified using statistical analysis. The approximately symmetrical breach hydrograph of the “November 3” Baige barrier lake could be partly attributed to the relatively fine grain size distribution of the dam material.